2001
DOI: 10.1046/j.1432-1327.2001.02237.x
|View full text |Cite
|
Sign up to set email alerts
|

Cell surface human α‐L‐fucosidase

Abstract: The acid a-l-fucosidase is usually found as a soluble component of lysosomes where fucoglycoconjugates are degraded. In the present investigation, we have demonstrated the existence of a cell surface protein with enzymatic a-l-fucosidase activity that crossreacts specifically with a rabbit anti-(a-l-fucosidase) Ig. By different approaches, this a-l-fucosidase, which represents 10±20% of the total cellular fucosidase activity, was detected in all the tested human cells (hemopoietic, epithelial, mesenchymal). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 43 publications
(58 reference statements)
4
26
0
Order By: Relevance
“…On the other hand, high levels of GDP-fucose (51) as well as cells positivity for fucosidase on the cell surface were actually detected in HeLa cells. (52,53). These considerations would, therefore, reinforce the attribution of the signal at 3.81 ppm of Fig.…”
Section: H-mrs Can Detect Aberrant Glycosylation In Hela Cellssupporting
confidence: 59%
“…On the other hand, high levels of GDP-fucose (51) as well as cells positivity for fucosidase on the cell surface were actually detected in HeLa cells. (52,53). These considerations would, therefore, reinforce the attribution of the signal at 3.81 ppm of Fig.…”
Section: H-mrs Can Detect Aberrant Glycosylation In Hela Cellssupporting
confidence: 59%
“…These lipids play key role as signaling molecules in both physiological and pathological processes regulating cell-to-cell and/or cell-environment interactions [3,38]. Several recent studies revealed the presence of glycohydrolases not only in lysosomes but also at cell surface [5,18,39,40]. They stress the potential role of a remodelling of glycosphingolipids during cellular processes [6,7].…”
Section: Discussionmentioning
confidence: 99%
“…ALFUC is an hydrolytic enzyme catalyzing the hydrolysis of terminal ␣-L-fucosidase linkages in glycosphingolipids and glycoproteins (29). Considering that cell-cell recognition involved in tissue differentiation and development is modulated by changes in the sugar chains of surface glycoproteins, and that deletion of ␣-fucosyl residues is one of such modulations, ALFUC can be assumed to play a role in tissue differentiation and development taking place during the process of cyclic recruitment, proliferation, and maturation of ovarian follicles.…”
Section: Discussionmentioning
confidence: 99%